2016
DOI: 10.1111/sipr.12017
|View full text |Cite
|
Sign up to set email alerts
|

Included but Invisible? Subtle Bias, Common Identity, and the Darker Side of “We”

Abstract: This article discusses how seemingly well-intended policies and interventions to reduce intergroup bias by emphasizing colorblindness through overarching commonalities between groups may, either unintentionally or strategically, inhibit efforts to address group-based inequities. First, we discuss the roots of bias in social categorization process, and how changing the way people think about group memberships from separate groups to members of the same group with shared identity improves intergroup attitudes. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
106
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 121 publications
(161 reference statements)
9
106
0
7
Order By: Relevance
“…Yet liking your oppressors deters protest. Numerous studies demonstrate that minority members who have experienced the most intergroup contact are in general more reluctant to protest for change (Dixon et al, 2010;Dovidio, Gaertner, Ufkes, Saguy, & Pearson, 2016;Saguy, Tausch, Dovidio, & Pratto, 2009;Wright & Lubensky, 2008; for a review see Becker & Tausch, in press).…”
Section: A Potentially Negative Effect Of Intergroup Contactmentioning
confidence: 99%
“…Yet liking your oppressors deters protest. Numerous studies demonstrate that minority members who have experienced the most intergroup contact are in general more reluctant to protest for change (Dixon et al, 2010;Dovidio, Gaertner, Ufkes, Saguy, & Pearson, 2016;Saguy, Tausch, Dovidio, & Pratto, 2009;Wright & Lubensky, 2008; for a review see Becker & Tausch, in press).…”
Section: A Potentially Negative Effect Of Intergroup Contactmentioning
confidence: 99%
“…In particular, superordinate identities often threaten subgroup identities, for example, by homogenizing differences between subgroups (Dovidio, Gaertner, & Saguy, ) and reflecting only a narrow range of the diversity of subgroups within the wider category (Wenzel, Mummendey, & Waldzus, ). Indeed, social psychological research has demonstrated that categorizing diverse and sometimes conflicting groups within a superordinate identity can sometimes exacerbate conflict, especially when there are existing power differences between subgroups (Dovidio et al, ; Dovidio, Gaertner, Ufkes, Saguy & Pearson, ). In a number of studies, Hornsey and Hogg () have shown that in contexts where people are categorized exclusively at the level of a superordinate group, they increase their efforts to differentiate their subgroups from each other and show more favoritism toward their own subgroup.…”
mentioning
confidence: 99%
“…The diversity paradigm, as applied to the U.S. context, for example, must replace normalized Whiteness, abetted by a binary either/or language, with an identity that enables Americanness to be multifaceted and inclusive (Dovidio, Gaertner, Ufkes, Saguy, & Pearson, ). Biculturalism (Chang, Hsu, Shih, & Chen, ; see also Gaither et al., ), dual‐identities (Gaertner et al., ), and intersectional analyses (Cole, ; Rosenthal, ) provide means by which multiple perspectives and understandings can be taken into account at the same time.…”
Section: Current Needs Challenges and Future Directionsmentioning
confidence: 99%